LAYANAN BIMBINGAN KELOMPOK DENGAN TEKNIK MODELING SIMBOLIK UNTUK MENINGKATKAN MOTIVASI BERPRESTASI SISWA KELAS VIII SMP PGRI NGAMPRAH - Putri Avriliani Nugraha; Teti Sobari; Ardian Renata Muardi (IKIP Siliwangi, 2026)
The study's overarching goal is to draw conclusions about how well symbolic modeling-based group mentoring motivates students to succeed. Students in a group setting that makes use of symbolic modeling techniques are more likely to internalize the positive actions and images that their guides portray, which in turn boosts their drive to succeed academically. The researchers in this study used a mixed-methods approach, which involves gathering both quantitative and qualitative information through interviews and observations. Eight individuals were selected at random from the entire student body to participate in the study. The research findings supported the research hypothesis, which states that students' achievement motivation was increased through group guidance using symbolic modeling techniques. This is supported by the T-test results, which show a t-count of -38.105 and a Sig level (2-tailed) of 0.000 < 0.05. In instance, symbolic modeling approaches might be viewed as having a significant impact on students' drive to succeed both before and after receiving group mentoring services..